Ectopic Pregnancy in a Non-Descript Goat - Namdeorao Bhadke, Gunwant; Fattuji Nipane, Suresh; Bhanudash Hatwar, Vitthal (The Indian Journal of Animal Reproduction, 2025)
Ectopic pregnancy denotes a pregnancy occurring outside the uterine cavity. This report presents a rare case of ectopic  pregnancy in a nondescript goat, in which the foetus protruded through the abdominal wall due to the rupture of the  uterine musculature peritoneum and muscle. Prompt surgical intervention successfully resolved the condition. The case  underscores the importance of early diagnosis and surgical management to ensure favourable outcomes.
Keywords: Ectopic pregnancy; Goat; Uterine rupture; Surgical management